Langerhans cell histiocytosis in children: the value of ultrasound in diagnosis and follow-up - Jinjin Yang; Xiaohua Huang; Zhongtao Bao; Jing Xu; Huimei Huang; Hongjie Huang; Ling Chen (BMC Medical Imaging)
Abstract Background Langerhans cell histiocytosis (LCH) is a rare disease, most prevalent in children. Ultrasound is a noninvasive, cheap, and widely available technique. However, systematic elucidation of sonographic features of LCH and treatment related follow-up are relatively few, resulting in overall underestimation of the clinical value of ultrasound in diagnosing and monitoring LCH. Objective This study aimed to observe the sonographic features of Langerhans Cell Histiocytosis (LCH) comparing with other imaging examinations, and to evaluate the changes of ultrasonography in the follow-up of LCH in children. Materials and methods Forty-four children (female:male, 19/25; median age, 60 months; range, 8 to 192 months) with LCH were included in this retrospective study. Thirty-one had single-system involvement (SS-LCH), and 13 had multisystem involvement (MS-LCH) among the 44 children. We analyzed the clinical characteristics, ultrasound (US) images, and images from other modalities, including X-ray, computed tomography (CT), and magnetic resonance imaging (MRI). The sonographic characteristics of the various involved organs, particularly bone, thyroid, and liver were analyzed, and the percentage of LCH cases correctly identified by the various imaging modalities were evaluated. Results Localized worm-like bone defects solid hypoechoic lesions were found in 38 patients with a total of 43 skeletal lesions, which showed solid hypoechoic lesions on US. Five patients showed hypoechoic or hyperechoic areas in the liver. Two patients showed scattered or diffuse irregular hypoechoic areas in the thyroid. Two patients with skeletal and 1 with thyroid involvement showed smaller lesions and lower blood flow after chemotherapy, and 6 lesions involving the liver resolved or were smaller in US review. The percentage of LCH cases correctly identified of US (65.38%) was higher than that of X-ray (21.05%) (P = 0.026) for skeletal lesions, which was comparable to that of CT and MRI. The overall correctly identified percentage of US for LCH was not significantly different from that of other imaging modalities. Conclusion LCH can be detected and suspected based on sonographic features. US may be an excellent tool for the diagnosis and follow-up of LCH in children.